2014
DOI: 10.1037/a0037950
|View full text |Cite
|
Sign up to set email alerts
|

The timing of entry into adult roles and changes in trajectories of problem behaviors during the transition to adulthood.

Abstract: This study of a cohort of 451 adolescents examined associations between trajectories of problem behaviors and the timing of entry into work, marriage, and parenthood. We used data from 12 assessments across adolescence, through emerging adulthood and into young adulthood. We employed 2-phase mixed-effects models to estimate growth in substance use and antisocial behavior across adolescence, deceleration in the period that follows, and the change point that marks the transition between the 2 phases. We then exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The present research examines the processes associated with escalation in substance abuse during the emerging adult years using a life course perspective. Studies informed by a life course perspective suggest that, for some young people, vulnerability to drug abuse is a developmental process and underscore the influence of challenging environments in childhood carries forward through intermediate mechanisms associated with the primary developmental milestones of successive developmental phases (Henry, Knight, & Thornberry, ; Martin, Blozis, Boeninger, Masarik, & Conger, ). Examinations of the processes through which vulnerability in an earlier developmental phase may affect downstream susceptibility are known as cascade models (Masten & Cicchetti, ).…”
Section: Life Course Theory and The Development Of Substance Abusementioning
confidence: 99%
See 1 more Smart Citation
“…The present research examines the processes associated with escalation in substance abuse during the emerging adult years using a life course perspective. Studies informed by a life course perspective suggest that, for some young people, vulnerability to drug abuse is a developmental process and underscore the influence of challenging environments in childhood carries forward through intermediate mechanisms associated with the primary developmental milestones of successive developmental phases (Henry, Knight, & Thornberry, ; Martin, Blozis, Boeninger, Masarik, & Conger, ). Examinations of the processes through which vulnerability in an earlier developmental phase may affect downstream susceptibility are known as cascade models (Masten & Cicchetti, ).…”
Section: Life Course Theory and The Development Of Substance Abusementioning
confidence: 99%
“…Precocious transitions evince strong associations with economic instability in emerging adulthood, characterized by suboptimal adaptation to social roles, closely related to economic distress (Martin et al., ). For example, adolescents leaving high school before graduation and entering job market at young ages may have unskilled, low‐paying jobs, which can produce economic instability.…”
Section: Inermediate Processes Linking Precocious Transitions To Downmentioning
confidence: 99%
“…Studies also suggest that, in low-resource communities, young adult marijuana use is viewed with greater concern than is evident in well-resourced communities because it is more likely to be associated with a high-risk lifestyle and affiliation with antisocial peers (Gibson, Perley, Bailey, Barbour, & Kershaw, 2015; Mawson, Best, Beckwith, Dingle, & Lubman, 2015). Thus, in the context of disadvantaged communities, conventional peers and adults are likely to withdraw from users, increasing the users’ alienation from sources of support associated with the diminution of substance use and related consequences among young adults (Bachman et al, 2012; Martin, Blozis, Boeninger, Masarik, & Conger, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In a different cross-sectional studies, Martins and colleagues found that compared to young adults (18–22 years old) enrolled in college, 18- to 22-year-old people not enrolled were significantly more likely to endorse NMUPO and less likely to endorse nonmedical prescription stimulants (NMUPS) [11]. Relevant to Martins’ findings is research showing that earlier entries into adult roles (e.g., foregoing university enrollment to enter the workforce) may be detrimental to individuals who are not well prepared for them [12]. However, some evidence demonstrates that employment is associated with decreased misuse of prescription drugs, as is the case among government employees and those whose employers had a drug-free workplace policy [13].…”
Section: Introductionmentioning
confidence: 99%